The influence of soil moisture, nitrogen fertilization, and temperature on quality and amino acid composition of Thatcher wheat - Hutcheon, W. L., author; Sosulski, F. W., author; Paul, E. A., author; Agricultural Institute of Canada, publisher (Colorado State University. Libraries, 1963)
The protein content of Thatcher wheat grown in the growth chamber was increased by reduced water supply, nitrogen fertilization, and higher air temperatures. Soil moisture conditions had a greater influence on protein content at higher temperatures, while the largest responses to nitrogen fertilization were obtained at the medium moisture level. Changes in sedimentation value and mixing time were associated with protein content except for plants grown at 62°F. Apparently the low temperature had an adverse effect on gluten quality. The relative distribution of 9 amino acids was significantly correlated with changes in grain protein content. Only 6 amino acids gave similar high correlations with flour protein content and sedimentation value. These differences are explained on the basis of changes in the morphology of the wheat grain and the proportion of flour proteins.
Keywords: environmental conditions; flour quality; soil moisture supply; sedimentation test; ion exchange chromatography